Cassava value chain development in West Africa: success stories - Sanni, Lateef O.; Onadipe, O.O.; Alenkhe, E.B.; Ilona, Paul; Davis-Mussagy, M.; Dixon, Alfred G.O. (International Association of Hydrological Sciences, 2012)
The initiative of cassava value chain in West Africa has provided sustainable opportunity for transferring best bet agronomic, processing and marketing practices to less privileged small holder enterprises in Nigeria, Benin and Sierra Leone. This project which started 2008, sponsored by Common Fund for Commodities, supervised by FAO and implemented by IITA has been an avenue to improve key players of cassava enterprise in the selected countries to boost their output qualitatively and quantitatively. The selected beneficiary processors individually and in groups were provided with well equipped renovated processing centers and business plans in 13 locations, thus creating enabling environments for maximum production of cassava products. They also received sound processing trainings on quality and competitive cassava products in addition to the introduction/development of new commercial cassava products for market diversification. The processors were as well provided with storage facility for finished products to enable an all year round access to products. The capacities of local fabricators were enhanced as they were used in fabricating all the equipment at the centers while markets were linked for the processors at all levels. From the assessment of the projects so far, appreciable and sustainable progress had been reported in term of processors' increased productivity, expanded utilization of cassava and capacity enhancement in processing and equipment management. The processing centers are being used as reference for academic and development purposes.